Inovasi Kreativitas Kepala Sekolah SMP Muhammadiyah 1 Surakarta untuk Menjadi Sekolah Unggul - Rochandhito, Hidayah; Inayati, Nurul Latifatul (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2023)
The purpose of this research is to explore the leadership process of a school principal to increase the principal's creative innovation at SMP 1 Muhammadiyah Surakarta and the obstacles encountered in the practice of school innovation. This research is a field research (field research). The author uses a type of field research, namely a phenomenological qualitative approach using data collection methods, observation, interviews and documentation. The results of this study seek the integration of all activities so as to be able to produce synergies to achieve efficient, effective and objective school goals. There are many excellent programs provided by school principals through their innovations at SMP 1 Muhammadiyah Surakarta in the form of Tahfidzul Quran, Memorization of the Qur'an, Memorization of Tajwid, Shirohnabawiyah. In practice, there are obstacles that are made to answer innovation problems, the student factor is the limited facilities in schools that are incomplete and there is no support from the local community and parents to carry out school innovation practices and there are limited insights, and narrow mindsets and lack of qualifications are obstacles in the application of innovation parquetk applied by the school principal. The Principal has an important role as an innovator. There needs to be support from the Principal in making improvements, and education staff must support and provide guidance so that they can develop optimally in carrying out the tasks that are their respective burdens. What is meant by creative is that in improving the professionalism of an educator, the principal must look for new ideas and ways of doing his job.